Jacob Have I Loved - Paterson, Katherine (New York Scholastic, 1990)
Feeling deprived all her life of schooling, friends, mother, and even her name by her twin sister, Louise finally begins to find her identity.
88748
Keywords: Twins -- Fiction; Sisters -- Fiction; Chesapeake Bay Region (Md. and Va.) -- Fiction